Rekayasa Teknologi Peningkatan Produksi Biomas Kerapu Macan (Ephinephelus fuscoguttatus) Melalui Penambahan Enzim Fitase Dalam Pakan Buatan - Diana Rachmawati (Universitas Gadjah Mada, 2012)
This study aims to examine the effects of phytase enzym in artificial feed on gowth, feeding usage and survival rate of brown marbled grouper (Ephinephelus fuscoguttatus) and to determine the optimum dose of phytase enzym in artificial feed on growth and feeding rate of brown marbled grouper (Ephinephelus fuscoguttatus) . Methodology used in this study was laboratory treatments with complete random design. The study consisted of four treatments and three repetitions. Treatment A (0 mg/kg of feed), B (500 mg/kg of feed), C (1000 mg/kg of feed), and D (1500 mg/kg of feed). Examined parameters were absolute weight growth, specific growth rate, feeding usage (feed and protein conversion ratio efficiency), survival rate and water quality. Varian analysis was used to analyze the data and Double Duncan Area Test was used to test the treatment differences. The results show that the treatments significantly (P<0.05) affected on the grwoth and feeding usage; however, they did not significantly (P>0.05) affect on the survival rate of brown marbled grouper (Ephinephelus fuscoguttatus). The optimum dose of phytase enzym for feeding usage and the growth of brown marbled grouper was 500-1000 mg/kg of feed. The water quality was still in the viable range for brown marbled grouper cultivation.